Polygraph testing in employment: concerns and challenges for South African labour law - Rossouw, Jeanne (Institute of Development and Labour Law, 2026)
The last number of years has witnessed an ever-increasing public awareness of the use of lie-detectors to uncover all forms of dishonesty, both in and out of the workplace. As much is evident not only from media coverage - ranging from advertisements for women's deodorant, to newspaper articles, but also from the increasing number of employment-related cases concerning polygraph testing to reach the Commission for Conciliation Mediation and Arbitration ("the CCMA"), and presumably also Bargaining Councils. Even national government agencies have made much publicized use of polygraph testing to screen prospective employees for employment positions.